Cluster randomized trial comparing school-based mass drug administration schedules in areas of western Kenya with moderate initial prevalence of Schistosoma mansoni infections. - Diana M S Karanja; Emmy K Awino; Ryan E Wiegand; Edward Okoth; Bernard O Abudho; Pauline N M Mwinzi; Susan P Montgomery; W Evan Secor (Public Library of Science (PLoS), 2017)
Mass drug administration (MDA) using praziquantel is the WHO-recommended approach for control of schistosomiasis. However, few studies have compared the impact of different schedules of MDA on the resultant infection levels. We wished to evaluate whether annual MDA was more effective than less frequent treatments for reducing community-level prevalence and intensity of Schistosoma mansoni infections.We performed a cluster randomized trial (ISRCTN 14849830) of 3 different MDA frequencies over a 5 year period in 75 villages with moderate (10%-24%) initial prevalence of S. mansoni in school children in western Kenya. Praziquantel was distributed by school teachers to students either annually, the first 2 years, or every other year over a 4 year period. Prevalence and intensity of infection were measured by stool examination in 9-12 year old students using the Kato-Katz method at baseline, each treatment year, and for the final evaluation at year 5. S. mansoni prevalence and intensity were also measured in first year students at baseline and year 5.Twenty-five schools were randomly assigned to each arm. S. mansoni prevalence and infection intensity in 9-12 year old students significantly decreased within each arm from baseline to year 5 but there were no differences between arms. There were no differences in infection levels in first year students either within or between arms.Strategies employing 2 or 4 rounds of MDA had a similar impact in schools with moderate initial prevalence, suggesting that schistosomiasis control can be sustained by school-based MDA, even if provided only every other year.